Analisis Bauran Pemasaran Terhadap Tahu Adibah Di Desa Sibalaya Barat - Nanda Alief Yudha Gunawan; Muh. Ali Murad; Risnawati Risnawati (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
Analysis of the marketing mix and the development strategy of the tofu agro-industry in Sibalaya Barat village. The research method used is a survey. The research respondents consisted of owners, employees, consumers, and the West Sibalaya village industrial office. The results showed that the marketing mix applied by the tofu industry at household, medium, and large scale for product mix, price, place, and promotion was different. The internal environment of the tofu industry consists of products, management, funding, human resources, business location, and marketing, while the external environment consists of economic, social and cultural, technology, competitors, government policies and consumers. The strategy for the development of the tofu agro-industry for medium and large households is the development of tofu production on a large scale because it is of interest to some people.